1984
DOI: 10.1017/s0024282984000347
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Copper Oxalate in Lichens Growing on Copper Sulphide-Bearing Rocks In Scandinavia

Abstract: Investigation of two sites in the Caledonian allochthon of the central part of the Scandinavian peninsula has shown that several copper tolerant lichens occur on cupriferous substrates. Analysis of the thalli of two of these species, Acarospora rugulosa and Lecidea theiodes, using atomic absorption spectroscopy, X-ray diffraction, infrared spectroscopy and electron probe microanalysis has revealed that copper occurs at high concentrations (5% Cu dry weight) principally as crystals of copper oxalate (1–5 μm dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 6 publications
1
76
1
Order By: Relevance
“…While biominerals such as moolooite found by Purvis (1984) have not been found in this study [51], formless particles rich in Fe and As have been found on the surface of the hyphae in the thallus. In addition, Fe, Cu, Zn, and As are distributed throughout the cells of the hyphae.…”
Section: The Accumulation and The Behavior Of Heavy Metals In The Liccontrasting
confidence: 53%
“…While biominerals such as moolooite found by Purvis (1984) have not been found in this study [51], formless particles rich in Fe and As have been found on the surface of the hyphae in the thallus. In addition, Fe, Cu, Zn, and As are distributed throughout the cells of the hyphae.…”
Section: The Accumulation and The Behavior Of Heavy Metals In The Liccontrasting
confidence: 53%
“…It has been demonstrated previously that some lichens can accumulate metals in considerable amounts, reaching more than 5% dry weight (Seaward 1973;Purvis 1984;Bačkor and Fahselt 2004a). Foliose lichen P. rufescens does not grow directly on mine heaps and is restricted to adjacent meadows where soils are lower in copper.…”
Section: Discussionmentioning
confidence: 92%
“…It is a widely distributed species occurring on siliceous or slightly basic rocks, and elsewhere in Europe on metalliferous rocks and in Pb-and copper-rich runoff from grilles on church walls (Purvis & Halls, 1996) and fence posts treated with copper\chromium\arsenic-bearing wood preservatives (Purvis et al, 1985). However, A. smaragdula is extremely variable morphologically and chemically, and its taxonomy is poorly understood (Clauzade et al, 1981), leading to the description of several subspecific taxa and, in cupriferous environments, species which are now regarded as ecotypes (Purvis et al, 1985 ;Purvis, 1996) (Purvis, 1984). Mechanisms of metal accumulation have already been established in species of Acarospora growing on metalliferous rocks using similar methods to those employed in the present study ; copper oxalate in A. rugulosa (Purvis, 1984 ;Chisholm et al, 1987) and copper-norstictic acid in A. smaragdula .…”
Section: mentioning
confidence: 99%
“…However, A. smaragdula is extremely variable morphologically and chemically, and its taxonomy is poorly understood (Clauzade et al, 1981), leading to the description of several subspecific taxa and, in cupriferous environments, species which are now regarded as ecotypes (Purvis et al, 1985 ;Purvis, 1996) (Purvis, 1984). Mechanisms of metal accumulation have already been established in species of Acarospora growing on metalliferous rocks using similar methods to those employed in the present study ; copper oxalate in A. rugulosa (Purvis, 1984 ;Chisholm et al, 1987) and copper-norstictic acid in A. smaragdula .…”
Section: mentioning
confidence: 99%